Performance Improvement of an Indirect Solar Dryer with Single Axis Manual Tracking System and Angular Simulation of the Flat Plate Collector Reflectors - Ajunwa, I.; Yawas, D. S.; Kulla, D. M.; Abdullahi, M. B.; Ibrahim, I. U.; Iorpenda Jnr., M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The need of food preservation cannot be over-emphasised. Crops need to be processed and preserved in times of their abundance to ensure for life and specie sustainability in times of scarcity. Flat plate collectors (FPCs) are often made fixed and the positions of reflectors used on them are not normally specified; in this paper, a report of an experimental test of an indirect solar dryer whose FPC is operated manually in a single axis to track the sun is presented. To avoid incurring extra cost on the existing design, the FPC was rather made to be operated manually instead of the automation process. Using the Engineering Equation Solver (EES) and the TRNSYS 16 softwares, the angular positions of reflectors placed east and west on the FPC were simulated for the first quarter months of the year of the experiment – this included the month of the test. This is to ascertain the best positions for the reflectors in other to achieve maximum insolation. For the month of the test, March, the angular positions of the reflectors placed east and west of the FPC were found to be 40° and 80° respectively relative to the horizontal plane. The performance of the solar dryer in terms of the percentage moisture loss, drying rate, collector efficiency and drying efficiency was evaluated when the FPC was fixed and when it was made to track the sun and the results obtained there from were compared. In comparison, it was found that the dryer tested by manually tracking the sun increased the total percentage moisture loss by 5.11%; the total drying rate by 2.10×10-5 kg/s; the average collector efficiency by 3.92% and the overall drying efficiency by 2.0% as compare to when the FPC was fixed, i.e. not tracking the sun. The indirect solar dryer with the ability to manually track the sun in a single axis using the meteorological conditions of Zaria, Nigeria was therefore found to have increased the performance of the system dryer as compare to when tracking of the sun was not done.